Related Factors to Patient Satisfaction on Meningococal Meningitis Vaccine Services at Palembang Class II Port Health Office - Pratiwi, Novy Stevani; Fatimah, Mustika; Sitindaon, Rina SE; Putri, Ririn Noviyanti (Journal of Midwifery and Nursing, 2024)
The implementation of international vaccination is one of the government's efforts to provide public protection through control of certain diseases in certain situations carried out at health facilities that organize international vaccination services. Health services quality should fulfill patient satisfaction because patient satisfaction is very important in assessing that quality. The purpose of this study was to determine the relationship between some factors such as age, gender, education, working, income, effective, patient-oriented, timely, and fair dimension with patient satisfaction on Meningococcal Meningitis Vaccination services at the Palembang Class II Port Health Office. This research uses an analytic research with cross sectional research design on 100 samples. The results showed that there was no relationship between age, gender, education and income while there was a relationship between working, effective, patient-oriented, timely and fair dimension with patient satisfaction. It is hoped that the results of this study can be used as evaluation material, especially in the quality of Meningococcal Meningitis Vaccination services at the Palembang Class II Port Health Office.